2020
DOI: 10.1101/2020.10.01.20205302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with access to virtual care in older adults: A cross-sectional study

Abstract: Background During the COVID-19 pandemic, virtual care (i.e. telephone or videoconference) has played a critical role. However, concerns were raised regarding equitable access for older adults, in particular, given potential advantages of videoconference- as opposed to telephone-based assessment. Our objective was to describe patient-specific factors associated with different modes of virtual healthcare. Methods We reviewed medical records of all patients assessed virtually in a geriatric medicine clinic in To… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Prior to the COVID-19 pandemic, US seniors engaged more in telemedicine, contacting physicians or filling prescriptions using telephone, cell phone or computers, despite regulatory restrictions (Levine et al, 2016). In regard to the modality of communication, older adults preferred telephone over videoconference (Levine et al, 2016), and recent work in a Canadian cohort indicated that frailty and absence of a caregiver were associated with lower likelihood for a videoconference assessment in seniors (Liu L et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic, US seniors engaged more in telemedicine, contacting physicians or filling prescriptions using telephone, cell phone or computers, despite regulatory restrictions (Levine et al, 2016). In regard to the modality of communication, older adults preferred telephone over videoconference (Levine et al, 2016), and recent work in a Canadian cohort indicated that frailty and absence of a caregiver were associated with lower likelihood for a videoconference assessment in seniors (Liu L et al, 2020).…”
Section: Introductionmentioning
confidence: 99%